DIAGNOSIS OF LEARNING DIFFICULTIES AND GUIDANCE LEARNING SERVICES TO SLOW LEARNER STUDENT - Rosada, Ulfa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
The failure to the learning process to reach ketuntasan material may not be returned in one factor , but on several factors involved in the process of teaching and learning. In the process diagnosis a learning disability what is important is finding the difficulty and types of difficulty teaching improvements conducted by effectively. A diagnosis is finding the a learning disability students and determine the possibility of how to overcome by taking into account the factors that affect the success of learning activities.